The Impact of Students’ Perception on their Academic Background on Their Learning Motivation - Rendhi Fatrisna Yuniar (JETLe (Journal of English Language Teaching and Learning), 2021)
Students’ academic performance is influenced by many factors such as previous academic background and level of motivation. There have been several studies trying to find out the correlation between students’ previous academic background and their learning achievement. However the results are not convincing. Though it is found out that there is correlation between students’ academic background and their learning achievement, the value of correlation is small. There have been also many researches investigating the impact of students’ motivation and their academic gain. However, the correlational study on students’ perception on academic background and their learning motivation is rare undertaking.